Understanding the Difficulties in Communication with Down Syndrome - ROSYIDAH, ROSSY HALIMATUN (English Education Department at FKIP Nommensen University, 2024)
The goal of this study was to identify the phonological difficulties a 19-year-old Down syndrome individual faced in her daily communication. The research method employed a qualitative descriptive approach using a case study design. A 19-year-old female with minor Down syndrome served as the research subject. Data was gathered using subject observation, interviews, and conversation recordings. The data was analyzed through some steps: first, transcribing the data; the recorded data is transcribed, the transcription process by writing the words spoken by the subject. Second, interpretation; the data was analyzed using relevant phonological process theory. The examination was conducted on the characteristics of language difficulties faced by subjects based on phonological theory. The result showed that the phonological difficulties faced by individuals with Down syndrome included the processes of assimilation, dissimilation, monophthongs, anaptyxis, substitution, apocope, and deletion of weak syllables.